Musculoskeletal disorders in public transportation workers of minor motorized vehicles of North of Lima: Trastornos musculoesqueléticos en trabajadores de transporte público de vehículos motorizados menores de Lima Norte - Becerra-Paredes, Nancy Yanet (2020)
Objective: To determine the frequency of musculoskeletal disorders (MSD) and its associated factors in workers of the public transport service of minors motorized vehicles of North Lima. Materials and methods: Quantitative and descriptive cross-sectional study. The study population consisted of public transport workers with minor motorized vehicles who worked in the districts of Los Olivos and Puente Piedra, belonging to North of Lima. The evaluation of the MSD was carried out with the Standardized Nordic Questionnaire. Results: A total of 300 workers of both sexes participated, with a mean age of 35.60 years (SD = 12; 16 Range: 17 to 70). Of the total sample, 94% (n = 282) were male, 61.7% (n = 185) were between 21 and 39 years of age. Regarding the presence of musculoskeletal symptoms, pain, discomfort, or discomfort in the lumbar and dorsal region were predominant, affecting 82.7% (n = 248) and 68.3% (n = 205), respectively. Among workers who presented pain, discomfort and discomfort in the lumbar region, 60.3% (n = 149) have worked every day (p = 0.011) and 46.2% (n = 114) have worked for 12 at 14 hours a day (p = 0.002). Conclusions: Among workers of the public transport service of minor motorized vehicles of North of Lima, there is a high prevalence of musculoskeletal disorders, mainly affecting the lumbar and dorsal areas of the body. An association of musculoskeletal disorders of the lumbar region was found with the frequency of days and hours of work. Keywords: Musculoskeletal system; Musculoskeletal pain; Ergonomics; Peru (Source: MeSH, NLM).